Smoking and Pulmonary Fibrosis: Novel Insights - Katerina D. Samara; George Margaritopoulos; Athol U. Wells; Nikolaos M. Siafakas; Katerina M. Antoniou (Pulmonary Medicine)
The relationship between smoking and pulmonary fibrosis is under debate and intense investigation. The aim of this paper is to review the existing literature and identify further areas of research interest. Recently the negative influence of cigarette smoking on IPF outcome was highlighted, as non-smokers exhibit a better survival than ex-smokers and combined current- and ex-smokers. In patients with non-specific interstitial pneumonia (NSIP), a high prevalence of emphysema was recently demonstrated, providing an indirect support for a smoking pathogenetic hypothesis in NSIP. The coexistence of pulmonary fibrosis and emphysema has been extensively described in a syndrome termed combined pulmonary fibrosis and emphysema (CPFE). Connective tissue disorders (CTDs) are a group of autoimmune diseases which affect the lung, as one of the most common and severe manifestations. However, the relationship between smoking and autoimmune disorders is still conflicting. Rheumatoid arthritis results from the interaction between genetic and environmental factors, while the best established environmental factor is tobacco smoking. Smoking has also a negative impact on the response of the RA patients to treatment. The aforementioned smoking-related implications give rise to further research questions and certainly provide one more important reason for physicians to advocate smoking cessation and smoke-free environment.